2017
DOI: 10.1002/etep.2372
|View full text |Cite
|
Sign up to set email alerts
|

Transmission network expansion planning using a modified artificial bee colony algorithm

Abstract: Summary Transmission network expansion planning (TNEP) problem is an essential part of power system expansion planning, and it is an extremely complex nonlinear, nonconvex, mixed‐integer optimization problem. Solution to such a computationally intensive problem is a challenge for any optimization algorithm. Consideration of security constraints makes the problem even more formidable. Although various conventional and metaheuristic methods have been used in the past to solve such problem, scope for better optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…based Ruddy turnstone optimization (ORTO) Algorithm and chaotic in-built Opposition based -Quantum Ruddy turnstone optimization (COQRTO) algorithm are corroborated in Garver's 6-bus test system, IEEE 30, 57, 118, 300, 354 bus test systems and Practical system -WDN 220 KV (Unified Egyptian Transmission Network (UETN)). At first proposed algorithm is reviewed in Garver's 6-bus test system [65]. It has six buses and lines, three generators and five loads [65] at buses.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…based Ruddy turnstone optimization (ORTO) Algorithm and chaotic in-built Opposition based -Quantum Ruddy turnstone optimization (COQRTO) algorithm are corroborated in Garver's 6-bus test system, IEEE 30, 57, 118, 300, 354 bus test systems and Practical system -WDN 220 KV (Unified Egyptian Transmission Network (UETN)). At first proposed algorithm is reviewed in Garver's 6-bus test system [65]. It has six buses and lines, three generators and five loads [65] at buses.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…At first proposed algorithm is reviewed in Garver's 6-bus test system [65]. It has six buses and lines, three generators and five loads [65] at buses. Table 1 shows the loss appraisal and Table 2 shows the voltage aberration evaluation.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As metaheuristic algorithm is a population dependant algorithm, a good variance in the population is needed for reaching the optimal solution. Hence, a value of the tuning parameter which exhibits a large variance of the population pool compared to the other settings is a good estimate for the optimal value of the respective parameter [34]. A few trials of the algorithm with lesser iterations per trial is enough for obtaining a good estimate as is shown in Tables 5 and 6.…”
Section: ) Parameter Tuning For the Mabc Algorithmmentioning
confidence: 95%
“…In this research work, the ACTNEP and RPP problems are solved using MABC algorithm [34], which is a general optimization algorithm developed from the artificial bee colony (ABC) algorithm [35], [36]. MABC is developed by incorporating the concept of universal gravitation [37] and global attraction [5] in the original ABC algorithm.…”
Section: Algorithm Used To Solve Tnepmentioning
confidence: 99%